Pengaruh Kepuasan Nasabah Terhadap Loyalitas Nasabah Pada Bank Rakyat Indonesia Kantor Cabang Ujung Batu - NISA, VINA OKTAVIA (Jurnal Mahasiswa Prodi Manajemen Fakultas Ekonomi, 2015)
The Purpose research this is the in order to find out whether be found effect satisfaction customer to loyalty customer Bank Rakyat indonesia and how great effect satisfaction customer to loyalty customer Bank Rakyat Indonesia. Data which be used is the Data primary and data secondary. Techniques Analysis data which be used in research this is analysis regression linear simple. From the analysis obtainable equation regression Y= 24.201 + 0.380 X. Analysis test t show that satisfaction customers influential on loyalty customer which shown by value significant 0.041 < 0.05 with value coefficient regression as big as 0.380%. Analysis of determination obtained value of R Square 0.141% which show that contribution value satisfaction is the as big as 14.1%, whereas the rest as big as 85.9% is influenced by factors other. With thus can be concluded that satisfaction customer affect loyalty customer